Treatment and disposal of piggery wastewater - Wong, Kien Keong; Chin, Kee Kean (1980)
This study reviewed extensively work done mainly on piggery wastes. Design criteria and performance for lagoon systems,oxidation ditch,activated sludge and anaerobic digestion,were presented. Reduction of BOD after anaerobic digestion was found to be as high as 85%. COD reduction was found to be lower. Secondary treatment following anaerobic digestion was recommended. Subsequent tretment after employing settling, flocculation and filtration to reduce the pollutant loading in the discharge were discussed. Reutilisation of treated wastes and waste products for animal feed,extraction of vitamins,fuel and fish breeding were also reported. Cost data on the construction of both bricks and reinforced concrete tanks were estimated.